Immature Skeletal Myotubes Are an Effective Source for Improving the Terminal Differentiation of Skeletal Muscle - Seung Yeon Jeong; Jun Hee Choi; Paul D. Allen; Eun Hui Lee (Cells)
Injured or atrophied adult skeletal muscles are regenerated through terminal differentiation of satellite cells to form multinucleated muscle fibers. Transplantation of satellite cells or cultured myoblasts has been used to improve skeletal muscle regeneration. Some of the limitations observed result from the limited number of available satellite cells that can be harvested and the efficiency of fusion of cultured myoblasts with mature muscle fibers (i.e., terminal differentiation) upon transplantation. However, the possible use of immature myotubes in the middle of the terminal differentiation process instead of satellite cells or cultured myoblasts has not been thoroughly investigated. Herein, myoblasts (Mb) or immature myotubes on differentiation day 2 (D2 immature myotubes) or 3 (D3 immature myotubes) were transferred to plates containing D2 or D3 immature myotubes as host cells. The transferred Mb/immature myotubes on the plates were further co-differentiated with host immature myotubes into mature myotubes in six conditions: Mb-to-D2, D2-to-D2, D3-to-D2, Mb-to-D3, D2-to-D3, and D3-to-D3. Among these six co-differentiation conditions, the D2-to-D3 co-differentiation condition exhibited the most characteristic myotube appearance and the greatest availability of Ca2+ for skeletal muscle contraction. Compared with non-co-differentiated control myotubes, D2-to-D3 co-differentiated myotubes presented increased MyoD and myosin heavy chain II (MyHC II) expression and increased myotube width, accompanied by parallel and swirling alignment. These increases correlated with functional increases in both electrically induced intracellular Ca2+ release and extracellular Ca2+ entry due to the increased expression of ryanodine receptor 1 (RyR1), sarcoplasmic/endoplasmic reticulum Ca2+-ATPase 1a (SERCA1a), and stromal interaction molecule 1 (STIM1). These increases were not detected in any of the other co-differentiation conditions. These results suggest that in vitro-cultured D2-to-D3 co-differentiated mature myotubes could be a good alternative source of satellite cells or cultured myoblasts for skeletal muscle regeneration.